Growth performance, nutrient utilisation and digestibility by Atlantic salmon (Salmo salar L.) fed Tasmanian grown white (Lupinus albus) and narrow-leafed (L. angustifolius) lupins - Michael Salini; LR Adams (2014)
Growth performance, nutrient utilisation and digestibility by Atlantic salmon (Salmo salar L.) fed Tasmanian grown white (Lupinus albus) and narrow-leafed (L. angustifolius) lupins